2016
DOI: 10.1039/c6nr04678a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic study on biodistribution and biodegradation of oral magnetic nanostructures in the rat gastrointestinal tract

Abstract: We have undertaken a magnetic study on the oral biodistribution and biodegradation of nude maghemite nanoparticles of 10 nm average size (MNP) and probiotic bacteria, Lactobacillus fermentum, containing thousands of these same nanoparticles (MNP-bacteria). Using AC magnetic susceptibility measurements of the stomach, small intestine, cecum and large intestine obtained after rat sacrifice, and iron content determination by ICP-OES, we have monitored the biodistribution and biodegradation of the maghemite nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…We can consider Xenopus as the bridge between cellbased assays and mammalian models taking into account that the activation of the iron metabolic pathway, especially with SC-DMSA, correlates with previous results in different murine models tracking IONPs biodegradation. 18,32,47 The significant increase of transcript levels of ferritin or dmt1 correlates with previous observations in a Wistar rat animal model where these proteins were quantified by ELISA in tissue samples from the liver, spleen and kidneys, 24 hours after SC-DMSA intravenous injection.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We can consider Xenopus as the bridge between cellbased assays and mammalian models taking into account that the activation of the iron metabolic pathway, especially with SC-DMSA, correlates with previous results in different murine models tracking IONPs biodegradation. 18,32,47 The significant increase of transcript levels of ferritin or dmt1 correlates with previous observations in a Wistar rat animal model where these proteins were quantified by ELISA in tissue samples from the liver, spleen and kidneys, 24 hours after SC-DMSA intravenous injection.…”
supporting
confidence: 85%
“…The application of AC magnetic susceptibility measurements has proven to be an excellent tool to study magnetic nanoparticles in complex matrices, since the diamagnetic signal coming from tissues does not interfere with the superparamagnetic signal of the NPs. 29 This way it was possible to follow the signal of the magnetic nanoparticles in animal models [30][31][32] and to quantify the iron content. This is one of the greatest challenges in the nanomaterials area nowadays, i.e.…”
mentioning
confidence: 99%
“…Although there are other parameters that may influence the location in temperature of the χ″(T) maximum, in this case, the main factor associated to this transformation is the reduction of the particle size due to the degradation process. 32,33 TEM observations showed that NPs@PMAO incubated in the lysosomal medium were degraded, in contrast to their PC-counterparts or the samples in water, that remained unalterable ( Fig. 3a).…”
Section: In Vitro Degradation Studymentioning
confidence: 99%
“…This biodistribution pattern could inspire us to develop their applications further in GI nanomedicine. 44 Liver injury markers such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) were also evaluated to investigate the risks of BSA@Bi 2 S 3 NPs. Although there was a slight disorder in AST at 14 day, all values of ALT and ALP were rather comparable with those of the control group.…”
Section: In Vivo Toxicitymentioning
confidence: 99%